Rise and shine eaudiobook - Quindlen, Anna (Recorded Books Inc., 2006)
It's Monday morning when Meghan Fitzmaurice blows her perfect life to bits. The host of "Rise and Shine," the country's highest rated morning talk show, Meghan cuts to a commercial break, but not before she mutters two forbidden words into her open mike. It's the end of an era, not only for Meghan, a household face who is not equipped to deal with disgrace, but for her younger sister Bridget, a social worker in the Bronx who has lived always in Meghan's long shadow. The effect of Meghan's on-air profanity-and truth telling-is felt by her son, her husband, her friends, her fans and even the city of New York, the capitol of appearance over reality. But above all it transforms the sister with whom she's shared everything, even the mixed blessings of fame. What follows is a story about a city big enough to hold prep school rappers, rich poseurs, familiar strangers, and autograph seekers in the ladies room at black tie balls. But ultimately it's about how, in very different ways, the Fitzmaurice girls whip the place into shape. Meghan and Bridget, Bridget and Meghan. They share smart mouths, a fractured childhood, and a powerful connection that even the worst tragedy can't rupture.